2014 55th International Scientific Conference on Power and Electrical Engineering of Riga Technical University (RTUCON) 2014
DOI: 10.1109/rtucon.2014.6998186
|View full text |Cite
|
Sign up to set email alerts
|

Study of generator modes effects on electric power quality and air gap

Abstract: The study examines hydroelectric power generator characteristics, voltage quality, air gap and vibration, in different operational modes -no-load mode, 90, 45, 10 MW load, 90 MW load with −50 MVAr to 20 MVAr reactive power and synchronous compensator mode with 0 MW-20 MW active power and synchronous compensator mode with −10 MVAr to −60 MVAr reactive power.Developed framework for power quality and air gap measurements assessment of hydropower generator shows that correlation exists between voltage, air gap and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…In our previous study [13] it was stated that for eccentricity evaluation the spectrum analysis should be used. From the frequency response theory it is known that frequency-domain considerations are applicable even when the signals are not periodic.…”
Section: Spectrum Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study [13] it was stated that for eccentricity evaluation the spectrum analysis should be used. From the frequency response theory it is known that frequency-domain considerations are applicable even when the signals are not periodic.…”
Section: Spectrum Analysismentioning
confidence: 99%
“…(2013) [16] found that correlations between the air gap, magnetic and vibration measurements performed for hydrogenerators are extremely important for detection of magnetic imbalance. In our previous study [13] a relationship was also established for the air gap and electromagnetic force (EMF) values, but the numerical correlation has not yet been obtained. The EMF-related unevenness of air gap [17] is the subject for future research.…”
Section: Evaluation Of Eccentricity By Plotting the Air Gap Values Fomentioning
confidence: 99%
See 2 more Smart Citations